Healing with animals in the Levant from the 10th to the 18th century - Lev Efraim (BMC, 2006)
Abstract Animals and products derived from different organs of their bodies have constituted part of the inventory of medicinal substances used in various cultures since ancient times. The article reviews the history of healing with animals in the Levant (The Land of Israel and parts of present-day Syria, Lebanon, and Jordan, defined by the Muslims in the Middle Ages as Bilad al-Sham) in the medieval and early Ottoman periods. Intensive research into the phenomenon of zootherapy in the medieval and early Ottoman Levant has yielded forty-eight substances of animal origin that were used medicinally. The vast majority of these substances were local and relatively easy to obtain. Most of the substances were domestic (honey, wax, silkworm, etc.), others were part of the local wildlife (adder, cuttle fish, flycatcher, firefly, frog, triton, scorpion, etc.), part of the usual medieval household (milk, egg, cheese, lamb, etc.), or parasites (louse, mouse, stinkbug, etc.). Fewer substances were not local but exotic, and therefore rare and expensive (beaver testicles, musk oil, coral, ambergris, etc.). The range of symptoms that the substances of animal origin were used to treat was extensive and included most of the known diseases and maladies of that era: mainly hemorrhoids, burns, impotence, wounds, and skin, eye, and stomach diseases. Changes in the moral outlook of modern societies caused the use of several substances of animal origin to cease in the course of history. These include mummy, silkworm, stinkbug, scarabees, snail, scorpion, and triton.